High bleeding risk patients. Issue 3 (30th January 2023) - Tarantini, Giuseppe; Cardaioli, Francesco
Key points: High bleeding risk (HBR) patients are generally more complex and affected by multiple comorbidities as compared to non‐HBR population. The Biofreedom DCS was successfully tested in this setting in previous randomized trials. In the present analysis, the Biofreedom DCS confirmed its good safety and efficacy profile also in a real‐world population of HBR patients, expanding the results also in non‐HBR subjects. However, despite a shorter DAPT regimen, HBR patients remain at higher risk for both ischemic and hemorrhagic events after PCI. Further randomized trials will be needed to fully explore the role of Biofreedom in non HBR patients and the best DAPT regimen for both HBR and non‐HBR subjects after PCI with Biolimus DCS.